Penyuluhan Kesehatan Pencegahan Anemia Pada Remaja Putri di SMPII Al Abidin Klaten - Agustin Mahardika Hariyadi; Rezyana Budi Syahputri; Nurul Dwi Andriani (Universitas Muhammadiyah Klaten, 2026)
Anemia remains a major health problem among adolescent girls because it can reduce learning concentration, productivity, and adversely affect future reproductive health. Limited knowledge regarding its causes, risk factors, and prevention prompted this community service program. The activity aimed to improve adolescent girls’ knowledge of anemia prevention through health education at SMPII Al Abidin Klaten. Conducted on Juny 2026, the program involved 31 female students from class VII C. The intervention consisted of a pre-test, health education using PowerPoint presentations, educational videos, discussions, the Kartu Milenial Sehat (KMS) Board Game, and a post-test. The mean knowledge score increased from 68.39 to 94.19, with an N-Gain score of 0.69 (moderate category). The Wilcoxon Signed Rank Test showed a significant difference between pre-test and post-test scores (p < 0.001). These findings indicate that interactive health education effectively improves adolescent girls’ knowledge of anemia prevention and can support sustainable school-based health promotion. Keyword: anemia, adolescent girls, health education, health promotion, anemia prevention.